2023
DOI: 10.7573/dic.2022-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nasal, pharyngeal and salivary secretory IgA levels in patients with COVID-19 and the possibility of correction of their secretion using combined intranasal and oral administration of a pharmaceutical containing antigens of opportunistic microorganisms

Abstract: Background Although extensive research has been conducted on the role of local immunity in patients with SARS-CoV-2, little is known about the production and concentrations of secretory IgA (SIgA) in different mucosal compartments. This article aims to assess the secretion of SIgA in the nasal and pharyngeal compartments and saliva of patients with COVID-19 and to investigate the possibility and efficiency of correction of their secretion using combined intranasal and oral administration of a phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Evaluation of clinical markers of effectiveness of Immunovac VP4 for IN-SC administration showed that in the Immunovac VP4 group the patients experienced a more significant reduction in inflammation on day 5, as seen by a statistically significant decrease in CRP, reduction in the duration of fever and the length of hospital stay. Thus, an analysis of the temperature reaction revealed that with IN-SC regimen of immunotropic drug administration, the duration of fever was also lower (1 [0.5–2] days) than in the control group of patients (4 [1–7] days, p = 0.002 but did not differ significantly from the group of patients receiving another—IN-per os (1 [from 0.5 to 2] day)—method of admission 19 . Comparing the duration of hospitalization stay (16 [13 to 19] days) administrating Immunovac VP4 in a combined IN-SC regimen with IN-per os use (16 [11 to 20] days) no differences were identified.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Evaluation of clinical markers of effectiveness of Immunovac VP4 for IN-SC administration showed that in the Immunovac VP4 group the patients experienced a more significant reduction in inflammation on day 5, as seen by a statistically significant decrease in CRP, reduction in the duration of fever and the length of hospital stay. Thus, an analysis of the temperature reaction revealed that with IN-SC regimen of immunotropic drug administration, the duration of fever was also lower (1 [0.5–2] days) than in the control group of patients (4 [1–7] days, p = 0.002 but did not differ significantly from the group of patients receiving another—IN-per os (1 [from 0.5 to 2] day)—method of admission 19 . Comparing the duration of hospitalization stay (16 [13 to 19] days) administrating Immunovac VP4 in a combined IN-SC regimen with IN-per os use (16 [11 to 20] days) no differences were identified.…”
Section: Discussionmentioning
confidence: 97%
“…Since we have already previously conducted a study of the assessment of mucosal immunity in IN—per os use of the Immunovac VP4 vaccine 19 , we were interested which way of administration of the drug is the most effective in the complex treatment of patients with COVID-19 associated lung lesions of moderate severity. The obtained results indicate that the levels of sIgA in the secretions of the salivary glands when prescribed an immunotropic drug according to IN and per os regimen during the entire observation period remain in high values: at the beginning of hospitalization 168.7 (95.8–233.8) mcg/l and 140.6 (86.4–213.4) and 154.6 (121.0–200.3) mcg/l after 14 and 30 days from the start of the vaccine, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation